Characteristics of Liquid Waste-Derived Organic Fertilizer Enriched With Oil Palm Empty Fruit Bunches Ash Through Anaerobic Fermentation - Rafi Mariska; Muhammad Faisal; Cut Meurah Rosnelly; Erisna Mirda (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2024)
Abstract: Palm oil mill effluent (POME) is an organic waste with high levels of BOD, N, P, K, and Mg. Its presence in rivers and soil has led to pollution and negative impacts on the environment. One potential solution to this issue is transforming POME into a valuable liquid organic fertilizer (LOF). This study aims to evaluate the characteristics of LOF derived from POME-derived LOF enriched with oil palm empty fruit bunches (OPEFB) ash through anaerobic fermentation. A 3.5 L of POME and molasses (5% v/v) were introduced into the anaerobic reactor. OPEFB ash was then added at concentrations of 0.35%, 0.46%, and 0.57% w/v. Fermentation was conducted for 5, 8, and 11 days, and Effective Microorganisms (EM4) with concentrations of 1% and 2% v/v were employed to accelerate LOF formation. The evaluation of LOF involved testing its physical characteristics (color, smell, gas, foam, temperature, and EC), fertilizer chemistry (pH, C-organic, Nitrogen, P2O5, and K2O), and biological aspects (contaminant bacteria E. coli). The results of the physical observations indicated that all LOF variations had fully fermented after 11 days, characterized by the presence of an alcohol-like odor, brownish color, absence of foam, and gas bubbles. Chemical tests revealed that LOF B2 and LOF A1, fermented for 8 days, exhibited the highest levels of N, P, and K, which were 0.08%, 0.05%, 1.26% for LOF B2, and 0.085%, 0.023%, 1.24% for LOF A1, respectively. Furthermore, the test result for E. coli in the LOF B2 and LOF A1 samples after 8 days of fermentation indicated that the E. coli level was below 3 MPN per mL. This confirms that the obtained LOF meets the minimum technical requirements specified in the Minister of Agriculture Regulation of the Republic of Indonesia. Therefore, the LOF is suitable for industrial-scale production and application in the agricultural sector.Abstrak: Limbah Cair Pabrik Kelapa Sawit (POME) merupakan limbah organik dengan kadar BOD, N, P, K, dan Mg yang tinggi. Kehadirannya di sungai dan tanah telah menyebabkan pencemaran dan memberikan dampak negatif terhadap lingkungan. Untuk mengatasi masalah ini, salah satu solusi potensial adalah mengubah POME menjadi pupuk organik cair (POC) yang bernilai tambah. Penelitian ini bertujuan untuk mengevaluasi karakteristik POC dari POME setelah penambahan abu Tandan Kosong Kelapa Sawit (TKKS) dengan metode fermentasi anaerob. Sebanyak 3,5 L POME dan tetes tebu (5% v/v) dimasukkan ke dalam reaktor anaerobik. Kemudian ditambahkan abu TKKS dengan konsentrasi 0,35%; 0,46%; dan 0,57% b/v. Fermentasi dilakukan selama 5, 8, dan 11 hari, dan Effective Microorganism (EM4) dengan konsentrasi 1% dan 2% v/v digunakan untuk mempercepat pembentukan POC. Evaluasi POC meliputi pengujian sifat fisik (warna, bau, gas, buih, suhu, dan EC), kimia pupuk (pH, C-organik, Nitrogen, P2O5, dan K2O), dan aspek biologi (bakteri pencemar E. coli). Hasil pengamatan fisik menunjukkan bahwa semua variasi POC telah terfermentasi sempurna setelah 11 hari, ditandai dengan adanya bau alkohol, warna kecoklatan, tidak adanya buih dan gelembung gas. Uji kimia menunjukkan bahwa POC B2 dan POC A1 yang difermentasi selama 8 hari menunjukkan kadar N, P, dan K tertinggi berturut-turut, yaitu 0,08%; 0,05%; 1,26% untuk POC B2; dan 0,085%; 0,023%; 1,24% untuk POC A1. Selanjutnya, hasil pengujian E. coli pada sampel POC B2 dan POC A1 dengan lama fermentasi 8 hari menunjukkan bahwa kadar E. coli di bawah 3 MPN per mL sehingga POC yang diperoleh telah memenuhi persyaratan teknis minimum (PTM) berdasarkan Peraturan Menteri Pertanian No. 261 Tahun 2019.